Investigation of the Relationship Between Fuel Prices and Fuel Consumption in Turkey - Suleymanli, Javid; Mammadov, Ilkin; Ahmadov, Fariz; Aliyev, Tabriz (International Journal of Energy Economics and Policy, 2022)
This study investigates the impact of fuel price changes on fuel demand in Turkey. The rise in global oil prices since the fourth quarter of 2021 has resulted in considerable increases in oil prices in countries that rely on foreign oil consumption. With the devaluation of the Turkish lira beginning the fourth quarter of 2021, the rise in oil prices reached a historical high in a very short period of time. This situation necessitates the presentation of a recent empirical study to the literature on whether oil consumption changes as a result of oil price fluctuations. Weekly data from 2014 to 2022 were analyzed for this purpose. The fuel expenditures of households with bank and credit cards were utilized as the dependent variable in the study to indicate fuel demand. The average of unleaded gasoline and diesel prices, car sales, car rental charges, and the nominal USD/TL rate are all considered independent factors. According to the analysis, an increase in the exchange rate and gasoline costs lowers the fuel price. The increase in expenses connected to car sales and rental, on the other hand, increases fuel costs.